Finger Painting untuk Meningkatkan Kreativitas Anak di KB Harapan Bangsa Guwo Tlogowungu Pati - Mudrikah, Mudrikah (Association of Indonesian Islamic Kindergarten Teachers Education Study Program, 2017)
This study aims to determine 1) the creativity of drawing children aged 3-4 years in KB Harapan Bangsa Guwo Tlogowungu Pati. 2) whether through finger painting can improve the creativity of drawing children aged 3-4 years in KB Harapan Bangsa Guwo Tlogowungu Pati. This research method uses classroom action research. This research is conducted in two stages, that is cycle I and cycle II. The subjects of this study were students of Harapan Bangsa Age Group 3-4 years Guwo Tlogowungu Pati as many as 17 students. The results of this study indicate that finger painting to enhance the creativity of childrens drawing is done with two cycles, the first cycle is done with F4 size paper media, free scratch technique, cycle II of the child is done with A3 size paper media and the technique of scratching fingers and grasping. The results of data analysis and observation through finger painting showed an increase from the pre cycle of 44% of children who completed the creativity of the drawing, up in the first cycle to 53%. That is, an increase of 9%. And in the second cycle increased to 80% and an increase of 84.6%. The results achieved in cycle II already meet the established completion target, which is 80% of the total children get the value with the category of the total value of 84.